Mycelium Bio-composites for Civil Infrastructure in Indonesia - Sihombing, Atmy Verani Rouly; Retno Utami; Luthfi Muhammad Mauludin; Nursyafril; I Nyoman Pugeg Aryantha; Syaiful Aulia Garibaldi; Fitria Dwi Ayuningtyas; Andro Mindo Matano Napitupulu; Mutiara Intan Rismaya (International Journal of Integrated Engineering, 2024)
Bio-composite is a composite produced from plants containing lignocellulose whose formation is assisted by fungal mycelium. This study aims to determine the proper method and composition to produce bio-composite that has structural strength for civil engineering buildings. The type of fungus used to produce mycelium is a white oyster mushroom which will be mixed in growing medium (substrate) containing lignocellulose and is commonly found in Indonesia as waste, namely: 1) sawdust; 2) rice husk; and 3) bagasse. The results of this study showed that bio-composite sawdust with white oyster mushroom mycelium at a composition of 7:9 which was printed using plastic at room temperature for 30 days and air-dried for two weeks could produce bio-composite with a compressive strength of 31.91 MPa, which is close to the compressive strength of paving blocks in general. This shows that the bio-composite sawdust in Indonesia has the potential to have structural strength.